The Relationship between Parents’ Literacy Beliefs and Practices and Children’s Responses to Literature - Mathew, Mincy Ruby; Singh, Sunita (JOURNAL OF INDIAN EDUCATION, 2023)
This qualitative case study investigated parental beliefs and practices regarding literacy, specifically, children’s literature and ways by which children respond to literature read aloud to them. It was conceptualised within the framework of family literacy and reader-response theory. The study was conducted by interviewing four mothers and their sixth-grade children, home observations and by conducting read-aloud sessions with children. Results of the study indicated a supportive, print-rich environment in the homes and the diverse ways by which participants engaged with children’s literature—by demonstrating intertextual, personal and expressive responses. The study highlights some pedagogical implications for teacher education programmes vis-à-vis family literacy practices.